Question:

Factor this term: 2x^2-2x-3?

by  |  earlier

0 LIKES UnLike

in 2 binomials...

 Tags:

   Report

4 ANSWERS


  1. 2x^2 - 2x - 3

    = cannot be factored in two binomials


  2. i dont have a pen and paper with me.. i dont think that its directly factorable.. so you have to use the quadratic formula for this.. let a=2, b=(-2) and c=(-3)...x=(-b±√(b^2-4ac))/2a

  3. 2x^2-2x-3 must be factored with the quadratic formula

    (This is assuming the expression is equal to zero):

    a = 2, b = -2, c = -3

    x = [-b± √(b²- 4ac)] / 2a

    = [ 2 ± √(4 - (4)(2)(-3)) ] / 4

    = [2 ± √(4 + 24)] / 4

    = [2 ± √28]/4

    = [2 ± 2√7] / 4

    = [1 ± √7] / 2

    This would make your factors

    (x - (1 + √7)/2 )(x - (1 - √7)/2 )

  4. 2x^2-2x-3

    ax^2+bx+c

    a = 2, b = -2, c = -3

    x = [-b± √(b²- 4ac)] / 2a

    = [ 2 ± √(4 - (4)(2)(-3)) ] / 4

    = [2 ± √(4 + 24)] / 4

    = [2 ± √28]/4

    = [2 ± 2√7] / 4

    = [1 ± √7] / 2

    This would make your factors

    (x - (1 + √7)/2 )(x - (1 - √7)/2 )

Question Stats

Latest activity: earlier.
This question has 4 answers.

BECOME A GUIDE

Share your knowledge and help people by answering questions.